Fe-Sn bimetallic catalysts for an enhanced Fischer-Tropsch synthesis stability via oxygen removal and coking resistance. (1st March 2022) - Gong, Huiyong; Qing, Ming; Wan, Hongliu; Yuan, Xiaoze; Qiao, Panzhe; Liu, Xingwu; Song, Xin; Wu, Baoshan; Wang, Hong; Wen, Xiao-Dong; Yang, Yong; Li, Yong-Wang
Graphical abstract: Sn-containing Fe5 C2 interface not only can boost the rates of oxygen removal but also restrain the coke deposition by elevating the barrier of nucleation, which stabilizes the active iron carbide structure and enhanced the stability remarkablely. Highlights: Oxygen removal by carbon oxide is facilitated for Fe-Sn interface； Coking deposition was inhibited remarkably for Fe-Sn bimetallic catalysts; Catalytic stability was significantly enhanced for Sn0.25 and Sn0.50 catalysts; Provided a strategy to construct durable catalysts under the perspective of oxygen removal and coking resistance. Abstract: Comprehending deactivation mechanisms and constructing durable Fe-based catalysts remain a substantial challenge for Fischer-Tropsch synthesis. In this contribution, the effects of Sn promoter on the structure and catalytic performance of Fe-based catalysts were investigated systematically. The catalytic stability was enhanced significantly for 100Fe/0.25Sn and 100Fe/0.50Sn catalysts, reducing the deactivation rate almost four-fold and seven-fold respectively. Combined with several characterizations and DFT calculation, it has been confirmed that Sn-containing Fe5 C2 interface not only can boost the rates of oxygen removal but also restrain the coke deposition by elevating the barrier of nucleation, which stabilizes the active iron carbide structure and inhibits the deactivation efficiently. This study may broaden the understanding of enhanced stability during Fe-based FTS under the perspective of oxygen removal and coking resistance and provide a strategy to construct durable catalysts.